R, Cultural Cultural Participation in a Pandemic Reality - Beata Reformat (Perspektywy Kultury, 2023)
The subject of the considerations was cultural participation in a pandemic reality and the resulting consequences and challenges for cultural institutions in Poland. Their identification was the main objective of the exploratory and problem-oriented article. The conclusions were based on rich literature, the results of research conducted by various specialized institutions in the form of reports and exemplification of selected practices used by cultural institutions in the field of access to cultural goods. The results obtained revealed changes in the ways and forms of cultural participation observed under the conditions of pandemic reality. The basis of their development is modern technologies that allow participation in culture in a hybrid way, allowing the reception of culture through online communication. In addition, based on the analysis, the key challenges facing cultural institutions in Poland were identified. The author’s intention was to identify possibilities for improving the activities of these entities in the new hybrid reality that most likely awaits us all in the coming years.